Differential Expression of VEGF-Axxx Isoforms Is Critical for Development of Pulmonary Fibrosis. - Barratt,SL; Blythe,T; Jarrett,C; Ourradi,K; Shelley-Fraser,G; Day,MJ; Qiu,Y; Harper,S; Maher,TM; Oltean,S; Hames,TJ; Scotton,CJ; et al. (American Journal of Respiratory and Critical Care Medicine, 2017)
RATIONALE: Fibrosis after lung injury is related to poor outcome, and idiopathic pulmonary fibrosis (IPF) can be regarded as an exemplar. Vascular endothelial growth factor (VEGF)-A has been implicated in this context, but there are conflicting reports as to whether it is a contributory or protective factor. Differential splicing of the VEGF-A gene produces multiple functional isoforms including VEGF-A165a and VEGF-A165b, a member of the inhibitory family. To date there is no clear information on the role of VEGF-A in IPF. OBJECTIVES: To establish VEGF-A isoform expression and functional effects in IPF. METHODS: We used tissue sections, plasma, and lung fibroblasts from patients with IPF and control subjects. In a bleomycin-induced lung fibrosis model we used wild-type MMTV mice and a triple transgenic mouse SPC-rtTA(+/-)TetoCre(+/-)LoxP-VEGF-A(+/+) to conditionally induce VEGF-A isoform deletion specifically in the alveolar type II (ATII) cells of adult mice. MEASUREMENTS AND MAIN RESULTS: IPF and normal lung fibroblasts differentially expressed and responded to VEGF-A165a and VEGF-A165b in terms of proliferation and matrix expression. Increased VEGF-A165b was detected in plasma of progressing patients with IPF. In a mouse model of pulmonary fibrosis, ATII-specific deficiency of VEGF-A or constitutive overexpression of VEGF-A165b inhibited the development of pulmonary fibrosis, as did treatment with intraperitoneal delivery of VEGF-A165b to wild-type mice. CONCLUSIONS: These results indicate that changes in the bioavailability of VEGF-A sourced from ATII cells, namely the ratio of VEGF-Axxxa to VEGF-Axxxb, are critical in development of pulmonary fibrosis and may be a paradigm for the regulation of tissue repair.